Respuesta :

Answer:

See the answers below

Step-by-step explanation:

Nine

The first step is to find the common difference. That's found by using

Common Difference

t4 - t3

t4 = - 15

t3 = - 19

t4 - t3 = -15 - - 19

t4 - t3 = -15 + 19

t4 - t3 = 4

t1 = - 27 which is the first term.

Explicit formula

tn = a + (n - 1)*d

tn = - 27 + (n - 1)*4

t5 = -27 + (5 - 1)*4

t5 = -27 + 4*4

t5 = - 11

Recursive

tn = tn - 1 + 4

Ten

Common difference

t4 - t3

21 - 15

Common difference = 6

t2 = 33 - 6

t2 = 27

Explicit formula

tn = a + (n - 1)*d

tn = 33 + (n - 1)*6

Recursive Formula

tn = tn-1  + 6

There are too many answers between the 2 questions that the exact format can be followed and have it make sense. You are better off following each question and writing down the answers as you come to them.